Мультиагентний підхід до моделювання інформаційно-аналітичної системи - Додонов, В.О.; Ланде, Д.В.; Путятін, В.Г. (Реєстрація, зберігання і обробка даних, 2016)
Розглянуто питання реалізації мультиагентного підходу до моделювання інформаційно-аналітичної системи, який реалізується у вигляді відповідної інформаційної технології, для подальшого застосування сценарного підходу. Представлено мультиагентну модель поширення інформаційних повідомлень, які містять посилання на інформаційні ресурси в мережі Інтернет. Результати моделювання підтверджено шляхом дослідження реальної мережі мікроблогів Twitter. Описано етапи створення корпоративної системи моніторингу мережевих інформаційних ресурсів, склад яких визначається посиланнями в мікроблогах. Наведено переваги такого підходу. Рассмотрены вопросы реализации мультиагентного подхода к моделированию информационно-аналитической системы, который реализуется в виде соответствующей информационной технологии, для дальнейшего применения сценарного подхода. Представлена мультиагентная модель распространения информационных сообщений, содержащих ссылки на информационные ресурсы в сети Интернет. Результаты моделирования подтверждены путем исследования реальной сети микроблогов Twitter. Описаны этапы создания корпоративной системы мониторинга сетевых информационных ресурсов, состав которых определяется ссылками в микроблогах. Приведены преимущества такого подхода. It is considered some questions of realization of multi-agent approach to modeling of information and analytical system which is realized in the form of the appropriate information technology, for to utilize further application of scenario approach. The multi-agent model of distribution of the information messages containing references to information resources on the Internet is provided. Characteristics of growth of quantity of special retweets of the chosen messages are analyzed. As a result of the described researches, the multi-agent model of distribution of the information messages containing references to information resources in the Internet is constructed. The results of modeling are checked by research of a real network of microblogs Twitter. The found regularities can be used when forming databases of information and analytical systems, when studying anomalies in statistics of references to separate information materials, and respectively, for identification of information transactions, artificially supported information campaigns.